Can Structured Intervention Improve Intercultural Communication in Multinational Student Teams? - Briguglio, Carmela (Marshall Cavendish Academic, 2006)
Group projects or group tasks are a common assessment task in undergraduate business education courses in Western Australia, largely due to educators' beliefs that such tasks develop valuable 'teamworking skills' that are much sought after by employers. The results, however, would seem to be somewhat mixed, with students sometimes reporting negative experiences in groups, particularly multicultural/multinational groups. Indeed, previous research (Hawthorne 1997; Nesdale & Todd 1997; Briguglio 1998; Valet & Ang 1998) indicates that if students are left to their own devices, they will often prefer to team up with others from similar nationalities/cultural backgrounds. In this 'Multinational Teams Case Study', it was decided to have students working in pre-structured multinational teams in order to mirror, as much as possible, the sorts of situations they are likely to meet in the world of work in future multinational companies/contexts. The Multinational Teams Case Study aimed to: 1. examine group interactions and identify communication issues in multinational student groupslteams; 2. establish whether a workshop providing students with insights and techniques for better intercultural communication and interaction in multinational teams actually has a positive effect on the nature of the group experience and the attitudes of students towards such teams.